Efektivitas Penggunaan Kahoot sebagai Alat Evaluasi Pembelajaran Siswa Sekolah Dasar - Khairunnisa Nasution; Monalisa Chaira Nainggolan; Muhamad Ahyar Fadly Siregar; Syahrial Syahrial (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine the effectiveness of using the Kahoot! application as a tool for student learning evaluation at the elementary school level. Using a literature review method, the researchers analyzed various relevant journals and scientific articles to assess the advantages, limitations, and impacts of Kahoot in the evaluation process. The findings indicate that Kahoot effectively enhances student motivation and participation, improves learning outcomes, and facilitates teachers in conducting interactive and enjoyable assessments. This application also supports the integration of online learning and can be flexibly used across multiple platforms. However, several challenges remain, such as limited internet access and the lack of ICT competence among teachers. Therefore, institutional support in the form of training and infrastructure provision is necessary to optimize the use of Kahoot in the learning process.